Literary Anti-Semitism and the Construction of an Image of the Jewish Nation in the Interwar Novels of the Broader Ostrava Region: Imagological-Comparative Study - Pěchula, Lukáš (Dějiny – teorie – kritika, 2019)
This analysis examines the construction of Jewish heteroimages and the impact of anti-Semitism on their construction in novels written between the two World Wars in the broader Moravian-Silesian region. It is a comparative study that explores Jewish ethnotypes employed in selected works by German and Czech authors of the period. The primary aim of the study is to discern images, to decode their structure, to analyze their functions in the text, and to examine the impact of anti-Semitism. The geographic focus is on the broader Moravian-Silesian region, which attracted Jewish immigration, and especially Ostrava, a multicultural city where people of Polish, Czech, German and Jewish nationalities lived side by side. It is precisely these specifics of the researched region, together with the interwar time focus of the work, that form an attractive basis for research.